Theoretical analysis on active radiant heat reflector integrated phase change material wall - Lee, Gyu-Bae; Cheon, Seong-young; Kang, Yong-Kwon; Kim, Beom-Jun; Joung, Jae-Won; Weon Jeong, Jae (CLIMA 2022 conference, 2022)
Recently, as interest in increasing energy efficiency of buildings increases, a method of reducin g indoo r hea t gain and los s b y integrating phas e change material s (PCM ) into building wal ls is bein g studie d. Th e PC M is a typ e of he at storag e materi al th at ca n redu ce energy consumption o f the cooling and heating devices o f the building by absorbing o r releasing heat from outside . However , th e PCM which i s integrate d int o th e wal l o f th e buildin g canno t fully achieve thermal performance because it absorbs or releases heat according to the temperature change of the surrounding members in the wall. To solve the problem, this study proposed a new system that improves the thermal performance of the PCM integrated wall by controlling radiant heat transfer inside of the wall. The proposed system adjusts the radiant heat transfer in the wall through a n activ e radian t hea t reflecto r, which control s surface emissivit y o f th e PC M i n the design conditions. To evaluate the proposed system, a numerical analysis for 1D transient heat transfer was used based on the energy balance equation for the indoor heat gain and loss with the reference systems. The simulation was conducted with Matlab 2021a software, and weather conditions were data from the summer (Jun-August) and winter (December-February) of IWEC2 Seoul. As a result of the simulation, the proposed system confirmed that indoor heat gains and losse s wer e improve d i n al l period s compare d t o th e reference system . Th e propose d system reduced the total indoor heat gain by 33.3%-44.1% in summer and the total indoor heat loss by 14.2-29.3 in winter compared to the reference systems.